La planificación presupuestal y el cumplimiento de metas en la Municipalidad Distrital de Jenaro Herrera, periodo 2023 - Vales Bartra, Alberto Agenor (2025)
This research was conducted with the aim of analyzing the relationship between budget planning and goal achievement. A descriptive-correlational approach and a non-experimental design were used. The sample consisted of 22 workers, to whom a questionnaire was applied to collect the necessary information. The results showed a significant relationship between strategic planning and tourism management, evidenced by a Pearson correlation coefficient of 0.728 and a significance of 0.01. Regarding the specific dimensions, budget diagnosis showed a correlation coefficient of (r=0.667; p=0.001), fund estimation had (r=0.627; p=0.002), and budget allocation presented (r=0.656; p=0.001), indicating that all are significantly related to goal achievement in the District Municipality of Jenaro Herrera.